Tesis Strategi Pengelolaan Kolaborasi Berbasis Masyarakat Terhadap Perlindungan Jenis Penyu Di Wilayah Pesisir Suaka Margasatwa Sidey Wibain, Kabupaten Manokwari, Provinsi Papua Barat: Penulis: Brian Stefano Irianto Korowotjeng, S.Hut brian85stefano@gmail.com Pembbimbing I: Prof. Dr. Etty Riani, M.S etty_riani_harsono@yahoo.com Pebimbing II: Prof. Dr. Erni Yuliana, S.Pi, M.T. ernik@campus.ut.ac.id Program Studi Magister Manajemen Perikanan, Universitas Terbuka - Brian Korowotjeng; Etty Riani; Erni Yuliana (Universitas Muhammadiyah Sorong, 2026)
Sidey Wibain Wildlife Sanctuary (SMSW) is a coastal conservation area that serves as nesting habitat for four protected sea turtle species: Green Turtle (Chelonia mydas), Olive Ridley (Lepidochelys olivacea), Leatherback (Dermochelys coriacea), and Hawksbill (Eretmochelys imbricata). Human activities such as poaching, egg harvesting, and land encroachment threaten turtle populations. This study aims to formulate a community-based collaborative management strategy. A qualitative descriptive approach was used, supported by SWOT and AHP analysis. Results show that while ecological conditions remain relatively intact, anthropogenic pressures are significant. BBKSDA Papua Barat plays the dominant role (20.60%), followed by indigenous communities (16.18%). Key strategies include strengthening collaborative institutions, empowering local communities, participatory monitoring, ecotourism development, and establishing a collaborative forum. Community-based collaboration is proven to be an effective and sustainable conservation model.